Comparison of Indonesian and US Bankruptcy Laws in the Protection of Creditors and Debtors : Perbandingan Hukum Kepailitan Indonesia dan Amerika Serikat dalam Perlindungan Kreditor dan Debitor - Anisa Defbi Mariana; I Gede Agus Kurniawan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Bankruptcy law functions as a collective debt resolution mechanism intended to balance legal certainty, economic stability, and fairness between creditors and debtors in modern business systems. Specific Background Indonesia regulates bankruptcy through Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, while the United States applies the U.S. Bankruptcy Code, particularly Chapters 7 and 11, reflecting different legal traditions and policy orientations. Knowledge Gap Despite extensive discussions on each system, systematic comparison focusing on creditor and debtor protection principles remains limited in highlighting structural and philosophical distinctions. Aims This study aims to compare the bankruptcy regimes of Indonesia and the United States with emphasis on mechanisms, principles, and legal protections afforded to creditors and debtors. Results The findings show that both systems recognize bankruptcy as a collective proceeding, apply creditor priority rules, and provide liquidation and reorganization pathways; however, Indonesia emphasizes procedural simplicity and creditor certainty, whereas the United States prioritizes debtor protection through automatic stay, debtor-in-possession, and reorganization-oriented frameworks. Novelty The study presents an integrated comparative analysis that links procedural design with underlying legal philosophy in both jurisdictions. Implications These findings offer a conceptual reference for bankruptcy law reform in Indonesia by identifying comparative elements that may support a more balanced protection structure for creditors and debtors within evolving economic conditions. Highlights: Both jurisdictions adopt collective debt settlement with structured creditor priority arrangements. Indonesia relies on simplified procedural thresholds, while the United States applies debtor-centered reorganization mechanisms. Divergent legal philosophies shape distinct institutional roles for courts, creditors, and debtors. Keywords: Bankruptcy, Creditor, Debtor, PKPU, Bankruptcy Law, Comparative Law